(untitled) (Jurnal Pendidikan Fisika, 2021)
This study aims to analyze the development of multimedia technology in physics learning based on the needs of the process and learning outcomes. This research is a literature review research. The research subjects consisted of ten journal articles selected from the Scopus Index database in the last five years. The results of data analysis show that learning physics with multimedia can stimulate students’ learning abilities well. The trend of research development shows that the use of multimedia in physics learning in Indonesia is growing rapidly at this time. In addition, multimedia learning physics is more on the content of introduction to solid matter physics, earth and space science, multimedia learning physics, experimental physics, electricity, modern physics, introduction to core physics, and quantum physics. The conclusion obtained from this analysis is that the level of multimedia needs in physics learning in Indonesia is still very high